(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Respiratory distress syndrome is a non-infectious pathological process in lungs developing in children in the first hours or days of life with acute respiratory failure caused by primary surfactant system failure, insufficiency of lung tissue, pathological processes taking place in lungs against the background of considerable suppression of vital functions of the body. Respiratory distress syndrome is one of the main causes of morbidity and death of premature and premature babies.